Umbilical artery Doppler velocimetry in pregnancies complicated by pregnancy induced hypertension. - Hettipathirana, P. S (My University, 2007)
To calculate the sensitivity, specificity and predictive values of RI, PI and SID ratio in predicting SGA babies in pregnancies complicated by PIR, And to determine which parameter serve as a better indicator in predicting SGA babies to asses perinatal morbidity in pregnancies complicated by PIR. Singleton pregnant mothers without any medical complications and diagnosed as having PIR was recruited at the anti natal clinic. It was done at POA of 30 - 32 weeks which was confirmed by ultrasound scan. Doppler wave form analysis of umbilical artery was done and these mothers were followed up till the delivery according to our unit protocol. At delivery birth weight according to the gestational age and other relevant data was collected in to a data collection form. Two hundred mothers were selected for the study .Taking the cut off value as. above 95th percentile for PI RI and above the value of 3 for SID ratio at 30-32 weeks as abnormal ,SID ratio got better values compared to PI RI, with a sensitivity of 78.7 percent specificity of 79.2 percent PPV of 69.4 percent and a NPV of 86.1 percent. In the management of pregnancies complicated by PIR, Doppler waveform analysis of umbilical artery can be used as an effective screening test at POA of 30-32 weeks in predicting SGA babies which is one of the main adverse out come. For this purpose the best index which we can use is SID ratio.